Employing telehealth strategies for opioid addiction during COVID-19: implications for social work health care. - Kim, Suk-hee; Tesmer, Olga (Social Work in Health Care, 2021)
As the COVID-19 global pandemic continues, more than 40 states have reported increases in opioid-related mortality. The issue of service access and delivery poses a major concern for those struggling with mental illness and substance use disorders in the United States. To ensure the continuity of health care during the pandemic and the co-occurring opioid crisis, the United States continues to adapt its healthcare delivery strategies, which include the introduction of telehealth. Telehealth is a relatively new concept and requires rapid systems changes as well as adjustments from both service providers and recipients. The proper adaptation to the new service delivery method could result in process optimization and improved outcomes for those struggling with opioid dependency. This study aims to bring attention to the opioid crisis that may be overlooked in light of the global pandemic and encourage social workers and other mental health professionals to utilize modern technological advancements to improve service delivery to their clients. This paper offers a literature review with four themes: (1) a retrospect on pain and opioids, (2) current telehealth models and practical strategies, (3) social work roles and functions in telehealth care, and (4) next steps and implications of telehealth for social work as a much-needed health-care delivery tool at the clinical and community social work practice level.